2021
DOI: 10.1186/s12957-021-02263-w
|View full text |Cite
|
Sign up to set email alerts
|

Improved perioperative outcomes and reduced inflammatory stress response in malignant robot-assisted colorectal resections: a retrospective cohort study of 298 patients

Abstract: Background Robot-assisted surgery is increasingly implemented for the resection of colorectal cancer, although the scientific evidence for adopting this technique is still limited. This study’s main objective was to compare short-term complication rates, oncological outcomes, and the inflammatory stress response after colorectal resection for cancer performed laparoscopic or robot-assisted. Methods We conducted a retrospective cohort study comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Improved levels of inflammatory markers postoperatively might provide a hint to a potential explanation for the beneficial patient outcome. Our observation of a decreased inflammatory stress response is in line with a previous study demonstrating a similar postoperative course of CRP levels between laparoscopic and robotic surgeries [ 19 ]. However, to confirm those results, prospective studies such as the SIRIRALS-Trial are necessary before final conclusions on potential mechanisms can be made [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Improved levels of inflammatory markers postoperatively might provide a hint to a potential explanation for the beneficial patient outcome. Our observation of a decreased inflammatory stress response is in line with a previous study demonstrating a similar postoperative course of CRP levels between laparoscopic and robotic surgeries [ 19 ]. However, to confirm those results, prospective studies such as the SIRIRALS-Trial are necessary before final conclusions on potential mechanisms can be made [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The mixed-effect model was adjusted for type of operation and time. The assumption of CRP among elective malignant colonic resections was based on postoperative measurements on days 1–3 from an observational data set of 298 patients undergoing surgery for colorectal cancer using robot-assisted or laparoscopic methods from 2017 to 2019 at our surgical department, Hospital Sønderjylland, University Hospital of Southern Denmark [ 17 ]. To obtain a power of 86% and an alpha level of 0.05 for a two-sided p-value, we aimed to include a minimum of 42 patients.…”
Section: Methodsmentioning
confidence: 99%
“…There is a direct correlation between high concentrations of pro-inflammatory cytokines and an increased mortality rate [ 11 , 13 ]. Non-randomized clinical trials have demonstrated that robot-assisted colorectal surgery has positive effects on faster establishment of bowel function and shorter hospital stay than laparoscopic surgery [ 14 17 ]. One study reported that robot-assisted surgery contributes to reduced surgical trauma due to better tissue exposure because of 3D-vision, wristed instruments and tremor reduction minimizing the inflammatory stress response, compared to the laparoscopic method [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other properties, such as parametrial and lymph node involvement, are also similar in the two groups. Another study by PedjaCuk et al (2021) compared the efficacy of robot-assisted colorectal surgery and laparoscopic colorectal surgery in terms of conversion rates, intraoperative blood loss, and morbidity and retrieval of bowel function [ 134 ]. A minimal conversion rate was observed in groups with ‘robot-assisted colorectal surgery’ due to the predominance of resection performed at the colon region.…”
Section: Comparative Efficacy In Clinical Outcomes Of Robot-assisted ...mentioning
confidence: 99%
“…Yet, this was non-significant for the rectal cancer patients who had undergone surgical resection using robot-assisted colorectal surgery [ 138 ]. Thus, with technical advancements, telerobotics, and ergonomics, robot-assisted colorectal surgery could be more advantageous than laparoscopic colorectal surgery to enhance overall long-term survival with minimal traumatization [ 134 ]. The advantages and disadvantages of robot-assisted surgery compared to conventional surgery is given in the following Table 4 .…”
Section: Comparative Efficacy In Clinical Outcomes Of Robot-assisted ...mentioning
confidence: 99%